Lifecycle framework for sustainable residential buildings in Malaysia - Ebrahimi, M.; Rahman, H.A.; Mohd-Rahim, F.A.; Chen, W. (Open House International Pub, 2014)
In Malaysia, there are a few numbers of frameworks and checklists in order to evaluate the sustainable performance of buildings. In addition, most of these assessment frameworks or checklists focus on environmental sustainability disregarding social and economic pillars. The research in social and economic sustainability in the construction industry is pushing forward, albeit at a slow pace. In addition, the growing number of sustainable criteria in the literature highlights the importance of a systematic framework for construction initiatives. This research aims to propose a comprehensive framework based on three pillars of sustainability, and, additionally, to categorize them in a manner that is applicable for all relevant stakeholders based on their level of involvement and needs. Finally, it identifies the relation between each criterion and stage of the construction lifecycle with the assistance of an expert panel. This research produces a framework that is useful for Malaysian construction stakeholders to reinforce their approach towards sustainability through social and economic aspects that are currently underestimated in the construction industry.